Erosion properties of tungsten and WTa5 alloy exposed to repetitive QSPA plasma loads below melting threshold - Makhlai, V.A.; Herashchenko, S.S.; Aksenov, N.N.; Byrka, O.V.; Garkusha, I.E.; Malykhin, S.V.; Surovitskiy, S.V.; Kulik, N.V.; Staltsov, V.V.; Lebedev, S.I.; Shevchuk, P.B.; Wirtz, M.; et al. (Вопросы атомной науки и техники, 2018)
The damage of deformed double forged pure tungsten (W) and tungsten alloyed with 5 wt.% tantalum (WTa5)
have been studied in experimental simulations of ITER-like transient events (surface heat load of 0.45 MJ/m²
and
the pulse duration of 0.25 ms) with quasi-stationary plasma accelerator QSPA Kh-50. The plasma exposures were
performed for targets maintained at room temperature and preheated at 200 or 300°C. The large and fine cracks
appeared in result of plasma impacts. The high number of repetitive plasma loads below the melting threshold led to
the clear degradation of thermo-mechanical properties of the affected surface layers on tungsten. Comparative
analysis of the cracks propagation to the bulk is presented for both W and WTa5 samples. Вивчено пошкодження деформованого подвійною ковкою чистого вольфраму (W) та з легуючою 5 об.%
домішкою танталу (WTa5) при експериментальному моделюванні умов перехідних процесів в ІТЕР (теплове
навантаження на поверхню 0,45 МДж/м²
, тривалість імпульсу 0,25 мс) у квазістаціонарному плазмовому
прискорювачі КСПП Х-50. Опромінення мішеней плазмою проводили при кімнатній початковій температурі
та з підігрівом до 200 та 300°C. В результаті плазмового впливу з’являлися великі й маленькі тріщини.
Велика кількість повторюваних плазмових навантажень нижча порога плавлення привела до явної
деградації термомеханічних властивостей пошкоджених приповерхневих шарів вольфраму. Представлено
порівняльний аналіз розповсюдження тріщин в об'єм для W- і WTa5-зразків. Изучены повреждения деформированного двойной ковкой чистого вольфрама (W) и с легирующей
5 об.% добавкой тантала (WTa5) при экспериментальном моделировании условий переходных процессов в
ИТЭР (тепловая нагрузка на поверхность 0,45 МДж/м²
, длительность импульса 0,25 мс) в
квазистационарном плазменном ускорителе КСПУ Х-50. Облучение мишеней плазмой проводили при
комнатной начальной температуре и с подогревом до 200 и 300°C. В результате плазменного воздействия
появлялись большие и мелкие трещины. Большое количество повторяющихся плазменных нагрузок ниже
порога плавления привело к явной деградации термомеханических свойств поврежденных
приповерхностных слоев вольфрама. Представлен сравнительный анализ распространения трещин в объем
для W- и WTa5-образцов.